2017
DOI: 10.1039/c7cc03378h
|View full text |Cite
|
Sign up to set email alerts
|

A targeted delivery strategy for the development of potent trypanocides

Abstract: A new drug delivery strategy was investigated for the development of potent anti-parasitic compounds against Trypanosoma brucei, the causative agent of African sleeping sickness. Thus, potent in vitro hexokinase inhibitors were rendered cytotoxic by appending a tripeptide peroxosomal targeting sequence that facilitated delivery of the molecular cargo to the appropriate organelle in the parasite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Historically, one of the key challenges in identification of anti-trypanosomal therapies that target glucose metabolism has been glycosomal segregation of relevant enzymes. A series of small molecule glycolysis enzyme inhibitors have been identified that were effective in vitro but less so against live cells, presumably because of limited delivery of inhibitors to the glycosomes in live parasites. , Our screening strategy bypasses the difficulty of glycosomal drug delivery because it identifies only molecules that effectively alter intraglycosomal glucose concentration. While many questions about the mechanisms of glucose delivery to the glycosome remain, the screening assay design will detect inhibitors without direct knowledge about individual transport mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, one of the key challenges in identification of anti-trypanosomal therapies that target glucose metabolism has been glycosomal segregation of relevant enzymes. A series of small molecule glycolysis enzyme inhibitors have been identified that were effective in vitro but less so against live cells, presumably because of limited delivery of inhibitors to the glycosomes in live parasites. , Our screening strategy bypasses the difficulty of glycosomal drug delivery because it identifies only molecules that effectively alter intraglycosomal glucose concentration. While many questions about the mechanisms of glucose delivery to the glycosome remain, the screening assay design will detect inhibitors without direct knowledge about individual transport mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…A series of small molecule glycolysis enzyme inhibitors have been identified that were effective in vitro but less so against live cells, presumably because of limited delivery of inhibitors to the glycosomes in live parasites. 10,23 Our screening strategy bypasses the difficulty of glycosomal drug delivery because it identifies only molecules that effectively alter intraglycosomal glucose concentration. While many questions about the mechanisms of glucose delivery to the glycosome remain, the screening assay design will detect inhibitors without direct knowledge about individual transport mechanisms.…”
Section: ■ Conclusionmentioning
confidence: 99%